DENSITY AND SOME ASPECTS OF REPRODUCTION FISH TEMBAKUL (Periopthalmus variabilis Eggert) IN THE COASTAL VILLAGE DISTRICT SAFE DARUL RUPAT DISTRICT BENGKALIS - Parnanda, Ario; Nasution, Syafruddin; Ghalib, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted in September 2014 in the coastal of Darul Aman Village Rupat District Bengkalis Regency. The Mudskipper (Periopthalmus variabilis Eggert) is one kind of fish are known to occupy beaches lined by mangroves. Mudskipper Fish has a bright prospect in the marine biotechnology industry such as food and pharmaceuticals. This study determined the density and reproductive aspects that include sex ratio, the level of gonad maturity, fecundity and diameter eggs located in the coastal of Darul Aman Village Rupat. The method used in this study is a survey method and made three square plots measuring 30 x 20 m2, for analysis in the laboratory using surgical methods, issued gonads and observe the gonads. The result show that the density of Mudskipper fish was low, the sex ratio was 2: 1 between male and female. All levels of gonadal maturity for female fish mostly at levels III, IV and V, whereas for male fish can be found at all levels (I-V). Fecundity values obtained ranged between 112.496-137.698 eggs and egg diameter sizes ranging from 0.235 - 0.55 μm.Keywords: Periopthalmus variabilis Eggert, Density Reproduction, Rupat